Effect of gamma oryzanol-rich fraction from purple rice extract against lipopolysaccharide-induced vascular endothelial growth factor C production of human colon cancer cells and angiogenesis of human umbilical vein endothelial cells - Panyathep, Atita; Punturee, Khanittha; Chewonarin, Teera (Agriculture and Natural Resources, 2022)
Importance of the work: Bacterial infection can be a critical event following operative resection of colorectal cancer (CRC) and is known to be associated with CRC metastasis. Angiogenesis is a metastatic process and is mediated by several angiogenic factors within cancer cells—especially the vascular endothelial growth factor C (VEGFC)—and the angiogenic steps of endothelial cells. Lipopolysaccharide (LPS) from infecting bacteria acts as a strong trigger of angiogenesis. Objective: To investigate the novel role of purple rice extract (PRE) on VEGFC production and the angiogenic process of LPS-stimulated colon cancer cells (SW480) and human umbilical vein endothelial cells (HUVECs). Materials and Methods: Hexane soluble fraction (HSF) collected from PRE (identified as the γ-oryzanol (OR)-rich fraction) and purified OR were tested in LPS-induced SW480 cells and HUVECs. The proliferative ability was determined using colony formation assay and succinate dehydrogenase activity (MTT) assay, while the secretion and expression of VEGFC were investigated using enzyme-linked immunosorbent assay and western blot, respectively. Cell migration and tube formation were identified based on wound healing and tube formation assays. Result: The inhibitory effect was confirmed of HSF on LPS responsiveness to VEGFC production in SW480, as well as in several angiogenic steps of HUVECs. Main finding: The OR-rich fraction from PRE could be used as a further novel supplementary option, alongside conventional therapy, to mitigate the effects of infection and to minimize the adverse consequences of CRC resection.